Testing Effects of Foreign Language Listening Anxiety on Chinese University Students' English Listening Test Performance - Liu, Meihua; Xu, Hongliang (Frontiers in Psychology, 2021)
The present research explored how foreign language listening anxiety (FLLA) affected Chinese university students’ English listening test performance in listening English and how demographic factorsproficiency and gender mediated the effects of FLLA on the latter. Two different populations from two universities in China answered the 20-item Foreign Language Listening Anxiety Scale (FLLAS) as well as a demographic questionnaire and took an English listening test. Analyses of the collected data collected revealed the following major findings: (a) Five latent factors underlay the FLLAS, (b) when working alone, FLLA significantly negatively predicted students’ English listening test performance in listening English, and (c) when working with demographic factorsproficiency and gender, English proficiency level, gender and FLLAS2 (proficiency in English listening English) significantly predicted students’ English listening English test performance. These findings indicate thatconfirm the FLLA negatively predicts effects of FLLA on students’ English listening test performance. in listening English and They also indicate that English proficiency level and gender mediate FLLA’s effects on the latter, with English proficiency not only directly but also indirectly affecting the latter.